Innovation and service outsourcing: An empirical analysis based on data from Tunisian firms - Hanen Sdiri; Mohamed Ayadi (Journal of Innovation and Entrepreneurship, 2016)
Recently, outsourcing services has been an important component of the organizational strategy of service firms. However, most research studies mainly focus on analyzing the determining factors of outsourcing at the expense of its structural effects. The aim of this paper is to examine the extent to which outsourcing relationships can be a source of service innovation by using a sample of 108 Tunisian service firms. Specifically, we are interested in the domestic outsourcing of auxiliary activities. Our results support the evidence of positive effects of outsourcing service activities on the capacity of innovation. This suggests that outsourcing allows Tunisian service firms to create value, increase flexibility and improve the quality of their services.
Keywords: D23; L21; L80; O31; O32; 650; Innovation; Outsourcing; Services sector